Securitized products, financial regulation, and systemic risk - Mariko Fujii (Asian Development Bank Institute (ADBI), 2010)
It is widely believed that the practice of securitization is one of the causes that led to the 2007-08 financial crisis. In this paper, I show that securitized products such as collateralized debt obligations (CDO) are particularly vulnerable to systematic risk and tend to show higher tail risk. These characteristics, in turn, are closely associated with joint failures and systemic risk. In order to achieve greater stability of the financial system, it is important to prevent the recurrence of the collapse of specific markets as this may lead to the collapse of other components of the financial system. From this perspective, the financial regulations that should be applied to these problematic financial products and their relation to possible systemic risks are discussed.
Keywords: G01; G11; G28; 330; Asset-backed security; Kapitalmarktliberalisierung; Wirkungsanalyse; Regulierung; Asien